The farmer in the Dell: Hi-Ho, the Derry-O, the current status of worldwide science mapping on precision irrigation (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Precision irrigation is essential to water-saving agricultural practices because agriculture and food are vital sectors for nations. This study evaluated how precision irrigation in agriculture is discussed in the current academic literature via science mapping of bibliometric data. A total of 967 documents spanning an 83-year publication timeline were accessed from the Scopus database using keywords related to precision irrigation. The extracted bibliographical information was analysed using Biblioshiny packages in R programming for trends, citation analysis, and intellectual structure. The findings show that precision irrigation research has grown over the past 20 years, with an average annual growth rate of 13.52% in publications. India is the most productive country in precision irrigation research, followed by China and the United States. Additionally, Hohai University has emerged as one of the top research institutions conducting precision irrigation research. In contrast, this study also shows that precision irrigation research has advanced from examining soil water and medium moisture content to creating an intelligent irrigation system to automate farmer decisions regarding crop water requirements and irrigation scheduling processes. These findings offer valuable insights for scholars seeking a deeper understanding of the global science mapping of precision irrigation for future research endeavours.
Keywords: bibliometric analysis; citation; precision irrigation; R packages; research trend; smart farming